The knowledge of nursing students about cervical cancer - José Antonio da Silva Júnior; Luana Larissa Oliveira Bezerra; Javanna Lacerda Gomes da Silva Freitas; Sheila Milena Pessoa dos Santos; Rodrigo Pinheiro Fernandes de Queiroga; Trycia Ryane de Freitas Silva (Universidade Federal de Santa Maria, 2021)
Objective: to analyze the knowledge of nursing undergraduate students about the risk factors and prevention of cervical cancer. Method: a cross-sectional, quantitative study, carried out with 112 nursing students from a public higher education institution in Northeast Brazil. Data collected in June 2017, using a structured questionnaire, with bivariate analysis between knowledge about the risk factors and prevention of cervical cancer and the sociodemographic, behavioral and academic variables. Results: there was an association between the undergraduate students' knowledge about risk and prevention factors and their participation in extracurricular activities, semester and assistance to women with an emphasis on cervical cancer. Conclusion: It is emphasized the need to improve the approaches to this theme in the undergraduate nursing course through the participation of students in extracurricular activities.